Homozygosity mapping and next generation sequencing for the genetic diagnosis of hereditary ataxia and spastic paraplegia in consanguineous families. (November 2020) - Jiao, Bin; Zhou, Zhifan; Hu, Zhengmao; Du, Juan; Liao, Xinxin; Luo, Yingying; Wang, Junling; Yan, Xinxiang; Jiang, Hong; Tang, Beisha; Shen, Lu
Abstract: Introduction: Genetic inheritance plays key roles in patients with ataxia and/or spastic paraplegia in consanguineous families. This study aims to clarify the genetic spectrum of patients with autosomal recessive hereditary ataxia and spastic paraplegias (AR-HA/HSPs) in consanguineous families. Methods: A total of 36 AR-HA/HSPs consanguineous pedigrees from China were recruited into this study. Next generation sequencing (NGS), guided by homozygosity mapping (HM), was applied to identify the pathogenic variants in known genes or novel candidate genes. Results: We totally made molecular diagnosis in 47.2% (17/36) of AR-HA/HSPs families. Among them, 13 AR-HAs carried pathogenic variants in SETX (n = 4), SACS (n = 2), STUB1, HSD17B4, NEU1, ADCK3, TPP1, PLA2G6 and MTCL1, while four AR-HSPs carried pathogenic variants in SPG11, ZFYVE26, ATP13A2 and ABCD1 . One homozygous nonsense mutation in MRPS27 was identified in an AR-HA family, which was potentially a novel candidate gene of AR-HA. Conclusion: HM and NGS can serve as an efficient molecular diagnostic tool for AR-HA/HSPs in consanguineous families. Our findings provide a better understanding of genetic architecture of AR-HA/HSPs in consanguinity and broaden the clinical-genetic spectrum of the disease. Highlights: Seventeen AR-HA/HSPs families were made molecular diagnosis using NGS and HM approaches. MRPS27 was a candidate gene for AR-HA. SETX mutation was more common in AR-HA families.